Tillich’s View on the Development of Capitalism (Part II) - Rachmat, Agus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2010)
Historically, the original impulse of capitalism is to be the emancipatory social power to liberate mankind from the fetter of Religious Leviathan reigning in the dogmatic Medieval Era. Ironically, after its historical global triumph, it becomes an Economic Leviathan of its own. The acute sense of structural sin and existential finitude nurtured by religious consciousness should make us aware of the hidden carnivorous dimension working deeply in the capitalist system that creates waste, crisis and destruction due to the cultivation of instant profit and unbridled greed as the moving forces of capitalism. KeyWords:*Watchman State, *Technical Reason, *Planning Reason, *Economic Leviathan, *Fascism, *Communism, *Global Capitalism, *SocialMarket, *Welfare State .